Crustal Deformation across the Jericho Valley Section of the Dead Sea Fault as Resolved by Detailed Field and Geodetic Observations. Issue 7 (13th April 2018) - Hamiel, Yariv; Piatibratova, Oksana; Mizrahi, Yaakov; Nahmias, Yoav; Sagy, Amir
Abstract: Detailed field and geodetic observations of crustal deformation across the Jericho Fault section of the Dead Sea Fault are presented. New field observations reveal several slip episodes that rupture the surface, consist with strike slip and extensional deformation along a fault zone width of about 200 m. Using dense Global Positioning System measurements, we obtain the velocities of new stations across the fault. We find that this section is locked for strike‐slip motion with a locking depth of 16.6 ± 7.8 km and a slip rate of 4.8 ± 0.7 mm/year. The Global Positioning System measurements also indicate asymmetrical extension at shallow depths of the Jericho Fault section, between 0.3 and 3 km. Finally, our results suggest the vast majority of the sinistral slip along the Dead Sea Fault in southern Jorden Valley is accommodated by the Jericho Fault section. Plain Language Summary: The Jericho Fault is a major section of the Dead Sea Fault near cities like Jerusalem, Amman, Ramallah, and Jericho. This study is dealing with the properties and behavior and of this active fault. We present geological observations and Global Positioning System (GPS) measurements of crustal deformation across the Jericho Fault section. The new observations reveal several slip episodes that rupture the surface, consist with strike slip and extensional deformation along a fault zone width of about 200 m. Using dense GPS measurements, we find that this section is locked for strike‐slip motion with a locking depth of 16.6 ± 7.8 km and a slip rate of 4.8 ± 0.7 mm/year. The GPS measurements also indicate asymmetrical extension at shallow depths of the Jericho Fault section, between 0.3 amd 3 km. Key Points: Field and geodetic observations along the Jericho Fault reveal strike‐slip and extensional deformation along a fault zone width of 200 m The Jericho Fault is locked for strike‐slip motion with a locking depth of 16 km and a slip rate of 4.8 mm/year GPS measurements indicate asymmetrical extension at shallow depths of the Jericho Fault, between 0.3 and 3 km